2008
DOI: 10.1016/j.biocon.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Social perceptions of the impacts and benefits of invasive alien species: Implications for management

Abstract: Research on biological invasions has traditionally focused on the ecological component of invasive alien species, either without considering or by considering in a restringing way, the knowledge of the social component. Understanding the human dimension of invasions is critical to effectively tackling the problems associated with invasive species. We used questionnaires to evaluate the social perceptions and attitudes of different stakeholder groups affected by invasive alien species in the Doñana social-ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
178
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(202 citation statements)
references
References 47 publications
(32 reference statements)
14
178
0
10
Order By: Relevance
“…There is still much to be learned about factors that influence knowledge, perceptions and practices relating to biological invasions (García-Llorente et al 2008). One framework suggests that the abundance of invasions is the dominant factor influencing perceptions (Shackleton et al 2007).…”
Section: Factors Shaping Knowledge Perceptions and Practices Of Promentioning
confidence: 99%
See 2 more Smart Citations
“…There is still much to be learned about factors that influence knowledge, perceptions and practices relating to biological invasions (García-Llorente et al 2008). One framework suggests that the abundance of invasions is the dominant factor influencing perceptions (Shackleton et al 2007).…”
Section: Factors Shaping Knowledge Perceptions and Practices Of Promentioning
confidence: 99%
“…Research on invasive species is normally approached from the domain of ecology, and more recently economics. Far less attention has been given to understanding the wider social dimensions of invasions (McNeely 2001;García-Llorente et al 2008, 2011. Insights on the human dimensions of invasive alien species are essential for effective decision making; in many cases, complex social issues delineate the full suite of benefits and costs associated with invasions (García-Llorente et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that older people, and those with higher levels of education were more supportive of higher levels of management intervention of INNP in parks (Sharp et al 2011). Conversely, other research has found that in south-west Spain younger people were more aware of concerns surrounding INNP (García-Llorente et al 2008). Ensuring communications about INNP are published in outlets accessible to a variety of age groups could help distribute knowledge more evenly.…”
Section: Drivers Of Perception Of Riskmentioning
confidence: 97%
“…Pesquisas sobre invasões biológicas têm sido tradicionalmente centradas nos componentes ecológicos das espécies não nativas, sem considerar ou por considerar de forma restrita, o conhecimento dos componentes sociais. A compreensão da visão humana sobre as invasões é fundamental para resolver os problemas associados às espécies não nativas (GARCÍA-LLORENTE et al, 2008). Segundo Larson et al (2011), para ser sustentável, a gestão de espécies invasoras deve abordar os fatores ambientais, sociais e econômicos (ou "pilares") que influenciam as causas, impactos e controle de espécies não nativas em várias escalas espaciais e temporais.…”
Section: Medidas De Prevenção E Controleunclassified